Depositional environments of tertiary turbiditic sediments in Metsovo Basin, NW Greece - ANANIADIS, G.; ZELILIDIS, A. (Bulletin of the Geological Society of Greece, 2018)
Tertiary sediments in Metsovo area consist of submarine fan turbidite deposits accumulated in the proximal part of the basin and represent mostly inner fan. The most proximal part of the inner fan could be related to a shelf environment. Palaeocurrent data indicate mainly two directions. The main direction is SW and results mainly from groove marks. The second direction represents an WNW trend which results mainly from flute marks. The Metsovo area seems to have multiple feeders from North and East. The total thickness of the turbiditic deposits in Metsovo area is approximately 6800 m due to tectonic stacking and folding.